Synergetic modulation of surface alkali and oxygen vacancy over SrTiO3 for the CO2 photodissociation. (30th November 2021) - Xu, Hua; Yan, Chunlei; Li, Ruizhe; Song, Lizhu; Ouyang, Shuxin
Abstract: Photochemical conversion of CO2 into solar fuels is one of the promising strategies to reducing the CO2 emission and developing a sustainable carbon economy. For the more efficient utilization of solar spectrum, several approaches were adopted to pursue the visible-light-driven SrTiO3 . Herein, oxygen vacancy was introduced over the commercial SrTiO3 (SrTiO3− x ) via the NaBH4 thermal treatment, to extend the light absorption and promote the CO2 adsorption over SrTiO3 . Due to the mid-gap states resulted from the oxygen deficiency, combined with the intrinsic energy level of SrTiO3, the SrTiO3− x catalyst exhibited excellent CO productivity (4.1 μmolˑg −1 ˑh −1 ) and stability from the CO2 photodissociation under the visible-light irradiation ( λ  > 400 nm). Then, surface alkalization over SrTiO3− x (OH-SrTiO3− x ) was carried out to further enhance the CO2 adsorption/activation over the surface base sites and provide the OH ions as hole acceptor, the surface alkali OH connected with Sr site of SrTiO3 could also weaken the Sr–O bonding thus facilitate the regeneration of surface oxygen vacancy under the light illumination, thus resulting in 1.5 times higher CO productivity additionally. This study demonstrates that the synergetic modulation of alkali OH and oxygen vacancy over SrTiO3 could largely promote the CO2 photodissociation activity.